How to Construct DNA Hydrogels for Environmental Applications: Advanced Water Treatment and Environmental Analysis. Issue 17 (16th February 2018) - Wang, Yingrong; Zhu, Yuan; Hu, Yi; Zeng, Guangming; Zhang, Yi; Zhang, Chang; Feng, Chongling
Abstract: With high binding affinity, porous structures, safety, green, programmability, etc., DNA hydrogels have gained increasing recognition in the environmental field, i.e., advanced treatment technology of water and analysis of specific pollutants. DNA hydrogels have been demonstrated as versatile potential adsorbents, immobilization carriers of bioactive molecules, catalysts, sensors, etc. Moreover, altering components or choosing appropriate functional DNA optimizes environment‐oriented hydrogels. However, the lack of comprehensive information hinders the continued optimization. The principle used to fabricate the most suitable hydrogels in terms of the requirements is the focus of this Review. First, different fabrication strategies are introduced and the ideal characteristic for environmental applications is in focus. Subsequently, recent environmental applications and the development of diverse DNA hydrogels regarding their synthesis mechanism are summarized. Finally, the Review provides an insight into the remaining challenging and future perspectives in environmental applications. Abstract : DNA hydrogels are very suitable for advanced water treatment and environmental analysis. Altering their components and structures, practical environment‐oriented DNA hydrogels can be designed in terms of environmental requirements. The strategies and mechanisms are introduced to produce the most suitable green, safe, and effective hydrogels.